2018
DOI: 10.1038/s41380-018-0108-3
|View full text |Cite
|
Sign up to set email alerts
|

New role of P2X7 receptor in an Alzheimer’s disease mouse model

Abstract: Extracellular aggregates of amyloid β (Aβ) peptides, which are characteristic of Alzheimer's disease (AD), act as an essential trigger for glial cell activation and the release of ATP, leading to the stimulation of purinergic receptors, especially the P2X7 receptor (P2X7R). However, the involvement of P2X7R in the development of AD is still ill-defined regarding the dual properties of this receptor. Particularly, P2X7R activates the NLRP3 inflammasome leading to the release of the proinflammatory cytokine, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 56 publications
(94 reference statements)
8
142
0
1
Order By: Relevance
“…Similar findings were reported for the cerebral cortex of spontaneously hypertensive rats, where the occlusion of the medial cerebral artery led to the upregulation of P2X7Rs in the penumbra surrounding the necrotic region (Franke et al, 2004). Thus, it was concluded that P2X7Rs induce proliferation of astrocytes upon their stimulation by ATP possibly released from the nearby, massively damaged CNS tissue (Franke et al, 2012;Franke and Illes, 2014;Martin et al, 2019).…”
Section: Microglial and Astroglial Functions; Cell Death And Prolifersupporting
confidence: 76%
See 2 more Smart Citations
“…Similar findings were reported for the cerebral cortex of spontaneously hypertensive rats, where the occlusion of the medial cerebral artery led to the upregulation of P2X7Rs in the penumbra surrounding the necrotic region (Franke et al, 2004). Thus, it was concluded that P2X7Rs induce proliferation of astrocytes upon their stimulation by ATP possibly released from the nearby, massively damaged CNS tissue (Franke et al, 2012;Franke and Illes, 2014;Martin et al, 2019).…”
Section: Microglial and Astroglial Functions; Cell Death And Prolifersupporting
confidence: 76%
“…A particularly intensively discussed issue is the transition of the cationic channel to a large membrane pore, because it appears to be essential for cytokine production and secretion (Illes et al, 2019;Martin et al, 2019). Originally, it was suggested based on equilibrium potential (V rev ) measurements with the whole-cell patch-clamp technique that the ion conducting pathway shows progressive dilation (Virginio et al, 1999).…”
Section: Purinergic P2x7 Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible pro-inflammatory pathways downstream of P2X7R activation include calcium-dependent PGE2 release, which has been implicated in sickness behavior 65 . In an Alzheimer's disease mouse model, P2X7Rs mediate beta-amyloid-induced chemokine release and lack of P2X7Rs reduces beta-amyloid deposition and improves synaptic plasticity and memory 66 . Furthermore, activation of P2X7Rs leads to the opening of accessory channels such as Pannexin1 (hemi)channels, which mediates ATP release and supports P2X7R activation within an inflammatory microenvironment 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Effet/impact de l'invalidation de P2X7R sur le développement de la MA Nous avons tout d'abord mis en évidence que, dans le cerveau de patients atteints de MA et dans un modèle murin développant des lésions amyloïdes (les souris transgéniques TgAPP/PS1 3 ), les cellules qui expriment fortement P2X7R étaient principalement les astrocytes et les cellules microgliales. Afin de déterminer le rôle de P2X7R dans la MA, nous avons donc évalué l'effet de l'invalidation génétique de P2X7R chez ces souris TgAPP/PS1 [7]. Nous avons montré dans ce modèle que la déficience en P2X7R diminuait la patho-…”
Section: Le Récepteur Purinergique P2x7unclassified